The use of verbal report methods in the development and testing of survey questionnaires - Willis, Gordon B.; Royston, Patricia; Bercini, Deborah (Applied cognitive psychology, 1991)
Increasingly, verbal report techniques are being used in the development and testing of survey questions. The present investigation examined the cognitive processes involved in responding to health survey questionnaires by conducting laboratory interviews which collected verbal reports. Analysis of these reports identified problems with questions that relate to the compre‐hension, recall, and decision processes the subjects used to answer those questions. This paper describes how questionnaire problems have been detected in the laboratory, and how these have been classified according to a cognitive model. We conclude that the laboratory verbal‐report techniques appear to be useful in detecting a variety of questionnaire flaws that are related to the operation of cognitive processes.